Achilles tendon stress is more sensitive to subject-specific geometry than subject-specific material properties: A finite element analysis. (3rd May 2017) - Hansen, Wencke; Shim, Vickie B.; Obst, Steven; Lloyd, David G.; Newsham-West, Richard; Barrett, Rod S.
Abstract: This study used subject-specific measures of three-dimensional (3D) free Achilles tendon geometry in conjunction with a finite element method to investigate the effect of variation in subject-specific geometry and subject-specific material properties on tendon stress during submaximal isometric loading. Achilles tendons of eight participants (Aged 25–35 years) were scanned with freehand 3D ultrasound at rest and during a 70% maximum voluntary isometric contraction. Ultrasound images were segmented, volume rendered and transformed into subject-specific 3D finite element meshes. The mean (±SD) lengths, volumes and cross-sectional areas of the tendons at rest were 62 ± 13 mm, 3617 ± 984 mm 3 and 58 ± 11 mm 2 respectively. The measured tendon strain at 70% MVIC was 5.9 ± 1.3%. Subject-specific material properties were obtained using an optimisation approach that minimised the difference between measured and modelled longitudinal free tendon strain. Generic geometry was represented by the average mesh and generic material properties were taken from the literature. Local stresses were subsequently computed for combinations of subject-specific and generic geometry and material properties. For a given geometry, changing from generic to subject-specific material properties had little effect on the stress distribution in the tendon. In contrast, changing from generic to subject-specific geometry had a 26-fold greater effect on tendon stress distribution. Overall, these findings indicate that the stress distribution experienced by the living free Achilles tendon of a young and healthy population during voluntary loading are more sensitive to variation in tendon geometry than variation in tendon material properties.